Governing REDD+: a state of the art review - Pinsky, Vanessa Cuzziol; Kruglianskas, Isak (Revista de Administração da UFSM, 2019)
Climate change is a daunting problem that results in actions-interactions from a number of actors in complex global systems, which require multi-level governance and a myriad of international and national policies. Deforestation is the second largest source of greenhouse gas (GHG) emissions. Success in this area can have a large impact on mitigation. We focus on the governance of ‘Reducing Emissions from Deforestation and Forest Degradation’ (REDD+), a large scale experiment in climate finance and a promising cost-effective mitigation mechanism to motivate developing countries to implement policy approaches to reduce forest-related GHG emissions. REDD+, in the context of strengthening the global response to the threat of climate change, is considered a breakthrough mechanism in international cooperation under the United Nations Framework Convention on Climate Change (UNFCCC) regime, as it was designed to be performance-based. In this paper we analyze a state of the art review on governing REDD+ based on a systematic analysis of peer-reviewed articles in the field. Ours results present a historical perspective of REDD+, literature review, and indicate the most relevant works and scholars in the field.